Evidence of fisher effect in South East Asian and Pacific Region - Bopulas, Brenda (2013)
This study intends to examine the validity of Fisher Effect on selected developing countries in South East Asia and Pacific Region. A total of 10 developing countries are selected which are Malaysia, Philippines, Papua New Guinea, Solomon Island, Thailand, Vanuatu, Tonga, Fiji, Vietnam and Indonesia. Quarterly data is used that start as early as 1990: 1 because this is the start of financial liberalization in most developing countries. Dependent variables used include nominal interest rate proxy by Treasury Bill Rate (TBR), Deposit Rate (DR) and Money Market Rate (MMR) depending on the availability data of respective countries. While Independent Variables used is Consumer Price Index (CPI) as a proxy for inflation rate. The empirical test that is used in this study is unit root test. The models that are employed are Autoregressive model to find the expected inflation and also Autoregressive Distributed lag model to determine the cointegration between both variables. The results show that only Thailand exhibits Fisher Effect while the other nine countries could not detect the existence of Fisher Effect.